Pembentukan Program Support System Injuri Spiritual dan Psikososial (Super Spesial) bagi Penderita Hipertensi - Mediarti, Devi; Sulistini, Rumentalia; Syokumawena, Syokumawena (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2023)
The increasing number of non-communicable diseases (NCDs) worldwide, makes it important to control and monitor patients with NCDs, especially hypertension. Handling Patients with Hypertension requires the role of a support system to be able to comply with the treatment. For this reason, it is necessary to form a Support System that knows and is able to provide solutions to family problems with hypertension, especially Spiritual, Psychological and Social. In this Community Service activity, it starts with screening the community with NCDs, meeting people with hypertension accompanied by their families and monitoring the evaluation of cadres, families as a support system. The results of this service activity are the formation of a family support system and cadres who know, understand and are able to provide education and support in the care of hypertension patients at home or in the community in spiritual, psychological and social aspects. This activity should be monitored continuously by health center and institutional staff.